Modeling the developmental origins of pediatric cancer to improve patient outcomes - James F. Amatruda (The Company of Biologists, 2021)
In the treatment of children and adolescents with cancer, multimodal approaches combining surgery, chemotherapy and radiation can cure most patients, but may cause lifelong health problems in survivors. Current therapies only modestly reflect increased knowledge about the molecular mechanisms of these cancers. Advances in next-generation sequencing have provided unprecedented cataloging of genetic aberrations in tumors, but understanding how these genetic changes drive cellular transformation, and how they can be effectively targeted, will require multidisciplinary collaboration and preclinical models that are truly representative of the in vivo environment. Here, I discuss some of the key challenges in pediatric cancer from my perspective as a physician-scientist, and touch on some promising new approaches that have the potential to transform our understanding of these diseases.